1988
DOI: 10.1089/jir.1988.8.35
|View full text |Cite
|
Sign up to set email alerts
|

Interferon InhibitsAspergillus fumigatusGrowth in Mice: An Activity Against an Extracellular Infection

Abstract: Prophylactic treatment of mice with interferon (IFN) or polyinosinic-polycytidylic acid [poly(I:C)], an IFN inducer, provided significant protection against an extracellular infection by Aspergillus fumigatus in both Swiss and Swiss athymic nude mice. Tunicamycin (TM) treatment inhibits the antifungal activity of IFN and poly(I:C) in these mice. Anti-asialo GM1 or TM [both inhibitors of natural killer (NK) cell function] treatment enhance the severity of A. fumigatus infection. These results suggest that NK ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…In a similar animal model, it was shown that NK cell-derived IFN-g was the protective factor against IA (8,9). Clinical data confirmed an antifungal and, more specifically, the anti-Aspergillus activity of IFN-g (7,(10)(11)(12)(13)(14). These studies attributed the beneficial effect of IFN-g to its immunoregulatory role with phagocytes of the innate immune system, which are conventionally involved in the host defense against A. fumigatus (11,15).…”
Section: N Atural Killer Cells Are Cd56mentioning
confidence: 79%
See 1 more Smart Citation
“…In a similar animal model, it was shown that NK cell-derived IFN-g was the protective factor against IA (8,9). Clinical data confirmed an antifungal and, more specifically, the anti-Aspergillus activity of IFN-g (7,(10)(11)(12)(13)(14). These studies attributed the beneficial effect of IFN-g to its immunoregulatory role with phagocytes of the innate immune system, which are conventionally involved in the host defense against A. fumigatus (11,15).…”
Section: N Atural Killer Cells Are Cd56mentioning
confidence: 79%
“…Increasing data provide evidence of direct NK cell action against extracellular pathogens, such as bacteria (4), parasites (5), and yeast (6). A role for NK cells and IFN against Aspergillus fumigatus in mice has been suggested (7). This was recently confirmed by Morrison et al (8), who showed that, in neutropenic mice with invasive aspergillosis (IA), the recruitment of NK cells was a critical host defense mechanism.…”
Section: N Atural Killer Cells Are Cd56mentioning
confidence: 92%
“…Despite the increasing incidence of fungal infections and their associated mortality, the presence and possible significance of type I IFN responses in these infections received little attention (11,12). Antifungal responses involving cytokines other than type I IFNs are becoming elucidated as to the fungal ligands, host cell receptors, and signaling pathways involved.…”
mentioning
confidence: 99%
“…Tunicamycin was employed once because of its anti-Natural Killer (NK) cell property (Maheshwari et al, 1988), and liposomal dichloromethylene diphosphonate (DMPD) because it decreases macrophages in liver and spleen (Moonis et al, 1994). Interestingly, 5 mg gold sodium thiomalate were injected 1 h before A. fumigatus inoculation in mice by Williams et al (1981).…”
Section: Resultsmentioning
confidence: 99%
“…For 24 of them, anti-neutrophil Ly6 (Gr-1) rat IgG 2b MAb57 antibody (clone RB6-8C5) was used on the basis of its property to react with mouse Ly-6G, i.e., a 21–25 kDa protein also known as the myeloid differentiation antigen Gr-1, for 24 of them (Supplementary Material 3). Some other antibodies, like anti-asialo GM1 and PK136, were injected to specifically study response due to NK cells (Maheshwari et al, 1988; Tandon et al, 1988; Morrison et al, 2003) or to target CD 4 + and/or CD 8 + T-cell lymphocytes (Corbel and Eades, 1977; Carvalho et al, 2012; Cruz et al, 2013). Some models described genetic rough depletion of all B-cell (Montagnoli et al, 2003) and T-cell lymphocytes (Maheshwari et al, 1988; Tandon et al, 1988).…”
Section: Resultsmentioning
confidence: 99%